Ekonomická a riziková analýza veřejného projektu v oblasti dopravních staveb - Hetfleišová, Natálie (Vysoké učení technické v Brně. Fakulta stavební, 2025)
Tato diplomová práce se zaměřuje na ekonomické hodnocení veřejného investičního projektu v oblasti dopravních staveb a následnou analýzu rizik. Konkrétně je předmětem práce projekt výstavby okružní křižovatky na silnicích II/306 a II/358 v obci Skuteč. Teoretická část práce se věnuje popisu veřejného investičního projektu, jednotlivým fázím jeho životního cyklu a charakteristice ekonomického hodnocení projektů. Dále jsou analyzována rizika spojená s realizací projektů, jejich klasifikace, identifikace, měření, řízení a provádění analýzy rizik. V rámci studie proveditelnosti je zpracován projektový záměr, SWOT analýza a logický rámec projektu. Následně je provedené ekonomické hodnocení projektu metodou analýzy nákladů a užitků CBA. Práce se zaměřuje na poskytování uceleného pohledu na rizika a hodnotu projektů v oblasti dopravní infrastruktury, což je zásadní pro proces rozhodování o jejich realizaci.

This master thesis focuses on the economic evaluation of a public investment project in the field of transport construction, followed by a risk analysis. Specifically, the subject of the thesis is the construction of a roundabout on roads II/306 and II/358 in the municipality of Skuteč. The theoretical part of the thesis addresses the description of public investment projects, the individual phases of their life cycle, and the characteristics of project economic evaluations. Additionally, it analyzes the risks associated with project implementation, including their classification, identification, measurement, management, and the execution of risk analyses. As part of the feasibility study, the project proposal, SWOT analysis, and the project's logical framework are developed. Subsequently, an economic evaluation of the project is performed using the cost-benefit analysis (CBA) method. The thesis aims to provide a comprehensive perspective on risks through sensitivity analysis and qualitative risk analysis, as well as on the value of transport infrastructure projects, which is crucial for decision-making regarding their implementation.
Economic and risk analysis of a public project in the field of transport constructions
Keywords: Veřejný investiční projekt; veřejná zakázka; životní cyklus projektu; dopravní infrastruktura; analýza nákladů a užitků; ekonomické hodnocení; efektivnost projektu; hodnocení rizik; Public investment project; public contract; project life cycle; transport infrastructure; cost-benefit analysis; economic evaluation; project efficiency; risk assessment